Is goodness without God good enough?: a debate on faith, secularism, and ethics - Garcia, Robert K. (Rowman & Littlefield Publ., 2009)
Introduction / Robert K. Garcia and Nathan L. King -- The Kurtz Craig Debate : is goodness without God good enough? / Paul Kurtz and William Lane Craig -- A moral argument for the existence of God / C. Stephen Layman -- Atheism as perfect piety / Louise Antony -- Is moral goodness without God rationally stable? / John Hare -- Why traditional theism cannot provide an adequate foundation for morality / Walter Sinnott-Armstrong -- Theism, atheism, and the explanation of moral value / Mark C. Murphy -- Empty and ultimately meaningless gestures? / Donald C. Hubin -- What difference does God make to morality? / Richard Swinburne -- This most gruesome of guests / a response by William Lane Craig -- Ethics without God : theism versus secular humanism / a response by Paul Kurtz